Design and Validation of a Multiplex KIR and HLA Class I Genotyping Method Using Next Generation Sequencing - Closa, Laia; Vidal, Francisco; Herrero, Maria J.; Caro, Jose L. (Frontiers in Immunology, 2018)
Killer cell immunoglobulin-like receptors (KIR), considered the most polymorphic natural killer (NK) cell regulators, bind HLA class-I molecules or still unknown ligands. Interest in KIR genotyping is increasing because of the importance of these receptors for identifying the best possible donor in hematopoietic stem cell transplantation to obtain a graft-versus-leukemia effect. Currently, routine protocols to determine the gene content of the KIR cluster are exclusively performed by PCR-SSO and PCR-SSP. To improve the study of these genes, we developed a multiplex, long-range PCR strategy suitable for simultaneous, high-resolution HLA class I and KIR genotyping by next generation sequencing (NGS). This protocol allows amplification of the 14 KIR genes, 2 KIR pseudogenes, and HLA class I genes, with subsequent sequencing on an Illumina platform. The bioinformatics analysis for KIR genotyping was performed by virtual hybridization of gene-specific probes, and HLA genotyping was done by GenDx NGSengine software. To validate the method reliability, 192 genomic DNA samples previously characterized by PCR-SSO were used. When a specific KIR gene was present, a large number of gene-specific virtual probes were detected, whereas when it was absent, very few or none were found, enabling cutoff establishment. Concordance for both the KIR and HLA assignments as compared with the previous characterization was 100%. In conclusion, the multiplex PCR NGS-based strategy presented could provide an efficient, less costly method for KIR-ligand genotyping by gene presence/absence. Furthermore, allele resolution will be possible when KIR-specific software becomes available.